Spellbound - Leighton, Georgia (Grand Central, 2025)
"In a remote castle perched atop a windswept island, a long-awaited royal heir is born. In accordance with ancient custom, a blessing ceremony takes place to bestow the princess with magical gifts - along with a terrible curse. Except this is not the love story you may think you know. There is no enchanted sleep for the princess, and no handsome prince to save the day. Just three women, who together concoct a desperate plan of misdirect that changes the course of all their lives. But dark magic cannot be tricked, and as the end of the curse edges closer, Violanna, Meredyth and Sel have a choice to make. They can wait to find out if the worst will happen, or they can turn to face the coming storm "-- Provided by publisher.